Molecular Mechanisms of Green Tea Polyphenols - Dou, Q. Ping (2009)
Tea, next to water, is the most popular beverage in the world. It has been suggested that tea consumption has the cancer-preventive effects. Epidemiological studies have indicated decreased cancer occurrence in people who regularly drink green tea. Research has also discovered numerous mechanisms of action to explain the biological effects of tea. The most abundant and popular compound studied in tea research is (−)-epigallocatechin-3-gallate or (−)-EGCG, which is a powerful antioxidant and can inhibit a number of tumor cell proliferation and survival pathways. Tea polyphenols are known to inhibit metaloproteonases, various protein kinases, and proteins that regulate DNA replication and transformation. We also reported that ester bond-containing tea polyphenols, for example, (−)-EGCG, potently and specifically inhibited the tumor proteasomal activity. We further demonstrated that methylation on green tea polyphenols under physiological conditions decreased their proteasome-inhibitory activity, contributing to decreased cancer-preventive effects of tea consumption. Since (−)-EGCG is unstable under physiological conditions, we also developed the peracetate-protected or prodrug form of (−)-EGCG, Pro-EGCG (1), and showed that Pro-EGCG (1) increases the bioavailability, stability, and proteasome-inhibitory and anti-cancer activities of (−)-EGCG in human breast cancer cells and tumors, demonstrating its potential use for cancer prevention and treatment.